PENGARUH ELEMEN EKUITAS MEREK TERHADAP KEPUTUSAN PEMBELIAN PISANG “SUNPRIDE” DI KOTA BANDAR LAMPUNG - Sujana, Utari Trina; Irianto, Heru; Khomah, Isti (Jurnal AGRISEP, 2020)
This research aims to analyze the effect of brand equity elements on the purchasing decision of "Sunpride" bananas in Bandar Lampung City. The basic method of this research is descriptive. The method of determining the location is purposive in Bandar Lampung City. The sampling using nonprobability sampling techniques, namely purposive sampling. The sample was 100 respondents. The analysis uses multiple linear regression analysis. The results indicate the elements of brand equity (brand awareness, brand associations, perceived quality, and brand loyalty) simultaneously have a positive effect on the purchasing decision of "Sunpride". Brand awareness, brand association and brand loyalty individually have a positive effect on the purchasing decision while the variable perceived quality has no effect. Known brands that have a relationship with health benefits and gain customer satisfaction will establish confidence in consumers to make purchasing decision of "Sunpride" bananas. Brand loyalty is the most influential variable on the purchasing decision of "Sunpride" bananas in Bandar Lampung City.